2015
DOI: 10.1039/c5ta03833b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plasma-induced graphene-sheet fibers from waste coffee grounds

Abstract: Microwave plasma-induced graphene-sheet fibers from waste coffee grounds showed potential applications for electrochemical conversion and storage with excellent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Thus, it is important to conduct research on CGs, in order to fully utilize and unlock their potential as the alternative materials for broad applications. CGs have been modified for various usages such as soil remediation, adsorbent materials, and electrochemical energy devices . In most of the cases, CGs need to be carbonized before their further utilization.…”
Section: Raman Information Of Gws Cg Area Pgs and Slg Based On Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to conduct research on CGs, in order to fully utilize and unlock their potential as the alternative materials for broad applications. CGs have been modified for various usages such as soil remediation, adsorbent materials, and electrochemical energy devices . In most of the cases, CGs need to be carbonized before their further utilization.…”
Section: Raman Information Of Gws Cg Area Pgs and Slg Based On Figmentioning
confidence: 99%
“…. This is due to the fact that more defects can be expected in our GWs, based on the obvious D and D′ peaks (structural defects or open edges) …”
Section: Raman Information Of Gws Cg Area Pgs and Slg Based On Figmentioning
confidence: 99%
“…4(b) . These results indicate that the NCNs prepared from 2-pyrrolidone may be composed of MLG with turbostratic stacking 37 39 . This turbostratic disorder was also apparent from the results of the X-ray diffraction (XRD), which found an interlayer spacing of 0.346 nm (bulk graphite: 0.335 nm) in the (002) diffraction peak (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…We utilized the microwave plasma irradiation technique to bombard biomass (rice husk and residual coffee grounds), in order to successfully fabricate different graphene-based carbon materials including vertical graphene, graphenated CNTs, which are graphene sheets grown on the walls of CNTs, and graphene-sheet fibers, which possess a large amount of defects and open edges (high I D /I G ratio). [81,82] Current experiments have confirmed that plasma-synthesized vertical graphene displays higher ORR performances than some N-doped CNTs, thus clearly confirming the significant contribution of carbon defects in electrocatalysis.…”
Section: Catalytic Properties Of Defective Nanocarbonsmentioning
confidence: 71%